2012
DOI: 10.1007/s00404-012-2573-2
|View full text |Cite
|
Sign up to set email alerts
|

The burden of anaemia and associated factors in HIV positive Nigerian women

Abstract: Anaemia was found to be high at 42.5 % among the HIV positive women studied and was found to be independently associated with short inter birth interval, presence of OIs, advanced HIV disease and use of zidovudine containing HAART regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Em gestantes infectadas pelo HIV, o uso da zidovudina é um risco em potencial para o desencadeamento da anemia materna 10 . A baixa contagem de linfócitos T CD4 está associada à anemia em gestantes infectadas pelo HIV 18 . Neste estudo, 12,9% das mulheres apresentaram contagens de células CD4 menores que 200 células/mm 3 .…”
Section: Resultsunclassified
“…Em gestantes infectadas pelo HIV, o uso da zidovudina é um risco em potencial para o desencadeamento da anemia materna 10 . A baixa contagem de linfócitos T CD4 está associada à anemia em gestantes infectadas pelo HIV 18 . Neste estudo, 12,9% das mulheres apresentaram contagens de células CD4 menores que 200 células/mm 3 .…”
Section: Resultsunclassified
“…9,10 Global cause-specific analysis have tended to focus only on tracking iron deficiency or on single country or region. [11][12][13][14] In view of magnitude and consequences of severe anemia, this study was planned with the aim to identify the significant socio-economic, demographic risk factors and etiology of severe anemia in Indian children of 6-59 months age by means of statistical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] These adverse pregnancy outcomes have been associated with low CD4þ counts, specific maternal infections, tuberculosis, malaria and opportunistic infections. 13,14 Measures to improve pregnancy outcomes include treatment with antiretroviral (ARV) drugs, multi-nutrient supplementation, vitamin A supplementation and intermittent preventive therapy for malaria in endemic areas. [15][16][17][18][19][20][21][22][23][24] Vitamin A supplementation in studies has not been shown to produce better outcomes in HIV positive women.…”
Section: Introductionmentioning
confidence: 99%